Exogenous application of glycinebetaine improves antioxidant system in green bean (Phaseolus vulgaris) seedlings under salinity stress - Srour, Hany A. M. (2015)
Salt stresses collectively are responsible for many crop losses worldwide especially salt - sensitive plants. The present study investigates the roles of exogenous application of glycinebetaine (GB, 5 mM) in improving salt stress tolerance in salt sensitive green bean seedlings. Salt stresses (45 mM NaCl for one week) significantly reduced leaf relative water (RWC) and chlorophyll (chi) content and increased percentage of electrolyte leakage, endogenous Proline and lipid peroxidation. Activities of peroxidase(PX), ascorbate peroxidae (APX), superoxide dismutase (SOD), and catalase (CAT), were significantly increased in shoots and roots of green bean seedlings subjected to salt stress. Exogenous application of GB improves salt tolerance of green been seedlings as shown by increased RWC and chlorophyll contents in leaves and reduced percentage of electrolyte leakage, lipid peroxidation and proline content. Under salinity stress condition, GB application decreased the activities of PX, CAT, APX and SOD in seedling shoots, whereas, it increased the activities of CAT and AP in roots. The result suggests that exogenous application of GB increased green bean seedlings' tolerance to salt-induced oxidative damage by upregulating their antioxidant defense system where this compatible solute protect plant cell against salinity stress. (Received 14 October
Includes references.
Summary in Arabic.
1
Keywords: Green bean -- Effect of salt on; Salinity; Antioxidants; Betaine; Salt-tolerant crops